Experimental Study of Joint Tool Variations in Cold Rolled Steel Structure Connection Systems C75 – 0,65 mm - Kuncoro, Hendrian Budi Bagus; Indianto, Andi; Putri, Mukhlisya Dewi Ratna (JURUSAN TEKNIK SIPIL, 2024)
C75 cold rolled steel is a material used in building construction with a lighter weight compared to conventional steel. One important aspect in the design of C75 light steel is the connection, where the connection must be designed safely so it is very important to maintain the structural integrity of the building and ensure the safety of building users. The aim of the research is to obtain the correct formulation for the C75 mild steel connection type in relation to the thickness of the C75 cold rolled steel. The method used is to create a connection system in the form of a variety of connections consisting of connections using screws only, combined screws and bolts, and connections using rivet nails. Overall, from the test results, it was found that the use of mild steel connections with a modified model between screws and bolts produced a greater value compared to using rivet connection tools alone or screws alone, this happened the same for every thickness of mild steel tested, both thickness 0, 65 mm, 0.75 mm or 1.00 mm. The greatest results were found in the connection of 4 screws and 1 bolt at a mild steel thickness of 1.00 to 100.00 N with a deflection of 2.58 mm. When compared with rivets, the increase reached 42.50%, while compared with screws, there was an increase of 20.00%. So rivet connections are brittle compared to screws and screw and bolt connections are a more ductile connection, so they can be recommended as connections in light steel. It's just that mild steel which has a greater thickness tends not to cause buckling compared to mild steel which is much thinner, where buckling is likely to occur in the mild steel material.